2008
DOI: 10.1186/ar2451
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity pulsed ultrasound activates the phosphatidylinositol 3 kinase/Akt pathway and stimulates the growth of chondrocytes in three-dimensional cultures: a basic science study

Abstract: Introduction The effect of low-intensity pulsed ultrasound (LIPUS) on cell growth was examined in three-dimensionalcultured chondrocytes with a collagen sponge. To elucidate the mechanisms underlying the mechanical activation of chondrocytes, intracellular signaling pathways through the Ras/ mitogen-activated protein kinase (MAPK) and the integrin/ phosphatidylinositol 3 kinase (PI3K)/Akt pathways as well as proteins involved in proliferation of chondrocytes were examined in LIPUS-treated chondrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 36 publications
4
82
0
Order By: Relevance
“…In vitro experiments have demonstrated that LIPUS stimulation affects mouse and rat osteoblast differentiation without influencing proliferation (8,9). Although the mechanisms involved have not been elucidated, LIPUS transmits signals into the cell via an integrin that acts as a mechanoreceptor on the cell membrane (16). The integrin/Ras/MAPK pathway is known to be a general pathway involved in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have demonstrated that LIPUS stimulation affects mouse and rat osteoblast differentiation without influencing proliferation (8,9). Although the mechanisms involved have not been elucidated, LIPUS transmits signals into the cell via an integrin that acts as a mechanoreceptor on the cell membrane (16). The integrin/Ras/MAPK pathway is known to be a general pathway involved in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the splicing protein TASR-1 attributes in removing exon 2 from Col2A [44]. Probably ultrasound mediated these effects via integrins and activativation of MAPK signaling and phosphorylation pathway [45]. Previous studies showed that phosphorylation modulates splicing proteins function [46] and stress stimulus resulted in changes splicing factors [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…The PC is a characteristic structure of the endochondral ossification processes, it is composed of highly organized cartilaginous tissue, it is located between the epiphysis and the diaphysis of the long bones and whose main function is the modulation of the longitudinal growth of the bone (van der Eerden et al, 2003). The PC is divided into three zones, each with distinctive morphological characteristics (Mackie et al, 2008), From epiphysis to diaphysis, we will find:…”
Section: Introductionmentioning
confidence: 99%
“…Nolte et al (2001) performed a morphohistological analysis on in vitro cultures of metatarsals after the application of LIPUS for 6 days, observing changes in the rate of bone growth expressed in an increase in the length of the diaphysial ossification center. It was hypothesized that this result could be explained by the activation of the PI3K / Akt pathway as the trigger for proliferation of chondrocytes mediated by LIPUS (Takeuchi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%